Perancangan Keamanan Server Linux Dengan Metode Hardening Pada Layer 1 dan Layer 7 - Maraghi Agil Prabowo; Ucuk Darusalam; Sari Ningsih (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Many person or institutions are still not aware of security on a server, not only rely on IDS and IPS applications and some firewall applications that we can easily find through internet networks. Special security handling is required on servers that are not related to third-party applications. The security design can be implemented through kernel configuration and tweaks that can be done by relying on the default application of an operating system. These applications are very common and can be found in almost all types of Linux server distributions. And there are still many people who do not maximize the security provided by the BIOS (Basic Input Output System) so that the operating system that has been installed and the data stored therein can be easily accessed by parties who are not responsible. Than as a preventive measure so that the data stored can not be accessed haphazardly by people who are not responsible, provided encryption and the sharing of system files that will be installed on the server. In the security steps for account access, the password that is created will be expired and the user cannot use the old password that he has used before